Naturally occurring beneficial bacteria Vibrio alginolyticus X-2 protects seaweed from bleaching disease - Mingyu Ma; Yingrui Zhuang; Lirong Chang; Luyang Xiao; Qin Lin; Qiying Qiu; Defu Chen; Suhelen Egan; Gaoge Wang (mBio, 2023)
ABSTRACT Microbiome manipulation is gaining fresh attention as a way to mitigate diseases in aquaculture. The commercially farmed seaweed Saccharina japonica suffers from a bacterial-induced bleaching disease, which has major implications for the reliable supply of healthy sporelings. Here, we identify a beneficial bacterium, Vibrio alginolyticus X-2 that significantly reduces the risk of bleaching disease. By combining infection assays and multi-omic analyses, we provide evidence to suggest that the underlying protective mechanisms of V. alginolyticus X-2 involve maintaining epibacterial communities, increasing the gene expression of S. japonica related to immune and stress protection pathways, and stimulating betaine concentrations in S. japonica holobionts. Thus, V. alginolyticus X-2 can elicit a suite of microbial and host responses to mitigate the bleaching disease. Our study provides insights into disease control in farmed S. japonica through the application of beneficial bacteria. IMPORTANCE Beneficial bacteria can elicit a suite of microbial and host responses to enhance the resistance to bleaching disease.